The Effect of Perineal Massage on Perineal Rupture Incidence On Primipara Mothers’ Labor In Kasih Ibu Clinic In 2020 - Cholisah Suralaga; Analia Analia; Sri Dinengsih (Universitas STRADA Indonesia, 2021)
There are various kinds of complications in the delivery process, one of which is the birth canal, namely perineal rupture. One of the ways to reduce perineal rupture is by performing perineal massage to improve health, blood flow, and perineal elasticity. This research was performed to examine the effect of perineal massage on perineal rupture among mother with primipara childbirth in Kasih Ibu clinic 2020. A quasi-experiment was used to conduct the current research by using post-test with control group design was conducted. There were 15 in the intervention group and 15 others in the control group. A total sampling was used. The independent t – test was used to identify the mean differences between groups. Results obtained that there was a significant effect of perineal massage on perineal rupture among mother with primipara labor in kasih ibu clinic 2020 with p-value = 0.009 (p-value < α = 0.05)